Система керування живленням електроприладів - Михальчук, М. О. (ХНУРЕ, 2022)
The Internet of Things is a variety of devices, ranging from the simplest, for example, devices to control lighting in the house, “smart” household sockets that can be controlled using a phone application, ending with more complex ones – a soil monitoring system. In this article the appliance power control system were proposed based on microcontroller ESP. For the data exchange in the proposed system the MQTT Protocol was proposed to use.